Histomorphometrical Evaluation of Fresh Frozen Bone Allografts for Alveolar Bone Reconstruction: Preliminary Cases Comparing Femoral Head with Iliac Crest Grafts. (7th January 2013) - Buffoli, Barbara; Boninsegna, Ramon; Rezzani, Rita; Poli, Pier P.; Santoro, Franco; Rodella, Luigi F.
Abstract Purpose In the past few years, the use of fresh frozen bone (FFB) grafts has significantly increased. The aim of this study was to evaluate the reconstruction of alveolar bone using femoral head and iliac crest FFB grafts. Materials and Methods The study included 10 patients who need endosseous implant insertion in severe atrophic maxillae. The patients were treated with FFB grafts collected from the femoral head or iliac crest. Bone regeneration was evaluated 6 months after surgery by macroscopic and microscopic analyses. Results Our results showed good regenerative capacity, both with the FFB from the femoral head and iliac crest. In particular, similar percentages of new‐bone formation and graft residual were observed, whereas differences between the percentage of total bone (higher for the iliac crest) and the percentage of non‐mineralized tissue (higher for the femoral head) were present. A significantly higher percentage of CD34‐positive vessels in the FFB allograft from the femoral head than in the iliac crest were observed. Conclusions These findings suggest that FFB allografts could represent a reliable option in oral and maxillofacial surgery. Nevertheless, differences between the use of femoral head or iliac crest bone allografts linked with their different structures should be considered for a more effective surgery.